(untitled) (New York, 2007)
The text is also designed to provide flexibility for instructors; the twelve chapters focus on the auditing process while the eight modules provide additional topics that can be taught at the instructor’s discretion without interrupting the flow of the text.
Keywords: Auditing,Kiểm toán